Emotion Regulation in Adolescents: Evidence of the Validity and Factor Structure of the Cognitive Emotion Regulation Questionnaire (CERQ) - Betegón, Elena (2022)
The Cognitive Emotion Regulation Questionnaire (CERQ) is an assessment tool to evaluate cognitive emotion regulation strategies. The main objective of this study is to provide new empirical evidence about the validity and reliability of the CERQ via a sample of 271 Spanish adolescents (136 female, 135 male) aged from 15 to 18 years (M = 15.7, SD = 0.76). The analytical process was carried out in two phases. A confirmatory factor analysis was performed on the polychoric correlation matrix between items. Four possible alternative models were contrasted: two models with nine factors and two models with two second-order factors and nine first-order factors, with 36 and 27 items, respectively. The model with nine correlated factors and 27 items obtained the best indices of overall fit. Subsequently, the reliability of the measurements was estimated on this model. The results reaffirm the validity of the 27-item version of the CERQ over the original 36-item structure. The findings also confirm that the CERQ is a reliable instrument for the evaluation of emotion regulation strategies in adolescents.